Acquisition of WNT Pathway Gene Alterations Coincides With the Transition From Precursor Polyps to Traditional Serrated Adenomas. (January 2019) - Hashimoto, Taiki; Ogawa, Reiko; Yoshida, Hiroshi; Taniguchi, Hirokazu; Kojima, Motohiro; Saito, Yutaka; Sekine, Shigeki
Abstract : Colorectal traditional serrated adenomas (TSAs) are often associated with precursor polyps, including hyperplastic polyps and sessile serrated adenoma/polyps. To elucidate the molecular mechanisms involved in the progression from precursor polyps to TSAs, the present study analyzed 15 precursor polyp-associated TSAs harboring WNT pathway gene mutations. Laser microdissection-based sequencing analysis showed that BRAF or KRAS mutations were shared between TSA and precursor polyps in all lesions. In contrast, the statuses of WNT pathway gene mutations were different between the 2 components. In 8 lesions, RNF43, APC, or CTNNB1 mutations, were exclusively present in TSA. RNF43 mutations were shared between the TSA and precursor components in 3 lesions; however, they were heterozygous in the precursor polyps whereas homozygous in the TSA. In 4 lesions with PTPRK - RSPO3 fusions, RNA in situ hybridization demonstrated that overexpression of RSPO3, reflecting PTPRK - RSPO3 fusion transcripts, was restricted to TSA components. Consistent with the results of the genetic and in situ hybridization analyses, nuclear β-catenin accumulation and MYC overexpression were restricted to the TSA component in 13 and 12 lesions, respectively. These findings indicate that the WNT pathway gene alterations are acquired during the progression from the precursor polyps to TSAs and that the activation of the WNT pathway plays a critical role in the development of TSA rather than their progression to high-grade lesions. Abstract : Supplemental Digital Content is available in the text.